Single Case Study on Pilonidal Sinus Using Madhu Saindhav Aragwadhadi Kshar Sutra, A Minimally Invasive Treatment. - Sharma, Mohan Swarup; Gupta, Rajesh Kumar (International Research Journal of Ayurveda & Yoga, 2022)
Pilonidal sinus (PNS) is a fissure between the buttocks (natal cleft) that can cause pain, embarrassment, and employment disruption. Men are more prone than women (because of the fact that men have more hair). Excision and primary closure, along with excision with reconstructive flap, are the most often adopted surgical methods for this condition. However, there is a substantial threat of recurrence or wound infection following the operation. In addition, the patient will have to stay for a longer period of time in the hospital, and the operation will be expensive. The Pilonidal sinus resembles the Shalya Nadi Vrana mentioned in the Sushruta Samhita. Sushruta has stated a less invasive para-surgical treatment for Nadi Vrana, known as the Kshar sutra technique. For a Vrana Shoshanna and Ropana activity for wound healing, Acharya Sushruta reviewed several herbs or herbo-mineral combinations. Among them drugs of aragwadhadi gan were used to prepare the kshar sutra along with madhu(honey), saindhav(himalayan salt) to lessen microbial burden, eliminates the unhealthy slough, necrotized tissue, and maintenance of wound moisture. As a result, this treatment was tested in the Pilonidal sinus, and the results are documented in this case report. The Kshar sutra procedure not only reduces recurrence and complications but also allows patients to return to work faster with less discomfort, has a significant effect on self-esteem & body image and is less expensive.